Legal Disharmony in Filling the Village Head Position Following Temporary Suspension in Sidoarjo - Putri Pangesti, Mayang (Jurnal Ad'ministrare: Jurnal Pemikirian Ilmiah dan Pendidikan Administrasi Perkantoran, 2025)
Village governance demands stable leadership to ensure the effective delivery of public services and development execution. However, a critical legal issue arises when a Village Head is temporarily suspended due to corruption charges, creating a transitional leadership vacuum. This study aims to comprehensively analyze the legal vacuum (lacuna legis) and regulatory disharmony regarding the filling of the Village Head position following temporary dismissal in Sidoarjo Regency, and to investigate the consequent socio-legal implications on village administration stability. The novelty of this research lies in its distinct focus; while existing literature largely discusses the criminal liability of corrupt village heads or the administrative procedures of dismissal, this study specifically isolates the "interim vacuum" phenomenon to demonstrate how regulatory gaps directly paralyze public service delivery during the legal process. Employing a socio-legal approach, this research integrates a normative analysis of Law Number 6 of 2014 and Sidoarjo Regional Regulations with empirical data obtained through in-depth interviews with officials from the Community and Village Empowerment Service, interim village officials (Plh), and community leaders. The results indicate a significant regulatory conflict where the appointment of a Daily Executive (Plh) provides only limited administrative authority, whereas an Acting Official (Pj) with full authority can only be appointed after permanent dismissal. Specific empirical evidence from Sidoarjo reveals that 71.4% of corruption-implicated villages are led by Plh who are legally restricted from making strategic decisions. This restriction has tangible negative impacts, including the inability to execute capital expenditures, leading to high remaining budget balances (SiLPA), stalled infrastructure projects, and bureaucratic paralysis due to internal resistance and fear of legal repercussions. Furthermore, the local government's attempt to bridge this gap through circular letters creates further legal ambiguity and risks of ultra vires actions. It is concluded that the current legal framework fails to address the transitional period effectively, resulting in a hostage situation for village development and a decline in public trust. To resolve this, this study recommends the revision of Minister of Home Affairs Regulation Number 82 of 2015 to formalize the authority of an Acting Officer (Plt) with limited strategic powers during temporary suspensions to ensure legal certainty and governance continuity.